Atomic spectrometry update: review of advances in the analysis of metals, chemicals and materials. Issue 11 (12th October 2018) - Carter, Simon; Clough, Robert; Fisher, Andy; Gibson, Bridget; Russell, Ben; Waack, Julia
Abstract : This review covers advances in the analysis of advanced materials, metals, fuels and lubricants, nano structures, ceramics, refractories, organic and inorganic chemicals, catalysts and nuclear materials by a range of techniques including X-ray, ICP, LIBS, mass spectrometry, synchrotron-based techniques, plus non-destructive and ablation surface techniques. Abstract : The use of LIBS continues to increase and many studies have been undertaken attempting to ensure maximum accuracy. This was especially true in the ferrous and non-ferrous metals sections where the spectra produced from the materials can be very line rich. Several papers described different mathematical algorithms to facilitate data handling. These included sequential backward selection – random forest, discriminant function analysis and genetic algorithms such as artificial neural networks. The use of such chemometric tools has also increased in sections including the analysis of cultural heritage samples, and the inorganic materials sections. In addition, it is still in common usage for dangerous samples, e.g. for explosives, nuclear materials etc. For the analysis of fuels, there is still a significant amount of wheel re-invention. Numerous papers are being published describing 'research', that are methods that have been in common usage in specialised fuels laboratories for some years. Sample preparation methods proved a popular area of research in this discipline. This is possibly a reflection of the necessity of analysing the different types of fuels now in common usage. The most recent pharmacopoeias are starting to describe the use of different atomic spectrometric techniques. There has therefore been an upsurge in the number of papers describing the analysis of pharmaceutical products. The lack of suitable reference materials for these and other organic-based sample types is problematic since method development has to rely largely on spike/recovery experiments. This review period has shown an increase in the number of papers using atomic spectrometry to elucidate mechanistic aspects of processes. This was especially true in the catalyst and electronic component sections. These studies frequently use several different techniques to obtain maximum information, e.g. oxidation state of the analytes, the surrounding chemical environment, bulk analysis etc. Foreword : this is the latest review covering the topic of advances in the analysis of metals, chemicals and materials. It follows on from last year's review 1 and is part of the Atomic Spectrometry Updates series. 2–6 This year has seen several changes to the writing team, with John Marshall and Ian Whiteside retiring. We are very grateful for their years of service. We welcome Julia Waack and Rob Clough who have contributed to various sections.